Conflict Resolution of Authoritarianism: Measuring the Stability of Human Rights Settlement Hegemony in Rohingya - Alfarisi, Muhammad Adib (Serikat Pengajar Hak Asasi Manusia Indonesia, 2024)
The Southeast Asian region has witnessed violent human rights violations in recent years with the 2012 Rohingya ethnic conflict in Myanmar. This has led to tensions between countries in the ASEAN region, which has an important influence on hegemonic stability in attempting conflict resolution or peace. This study expresses the power of conflict resolution in the Southeast Asian region over human rights violations in Rohingya, which is a qualitative study using the theory of conflict described by Galtung regarding peace. Theoretically, this research has the hegemonic power needed to create international system stability and security in the ASEAN region. The Rohingya conflict caused many refugees to transmigrate to neighboring countries. This condition is a security concern in the Southeast Asian region to be unstable. Therefore, hegemonic power is needed to create stability in the ASEAN region. On this basis, ASEAN addresses several problems among its member countries and strengthens cooperation and the rule of law in the international world regarding human rights. So that Southeast Asian countries through conflict management, from military, economic, political, ideological, and institutional as one of the hegemonic forces between ASEAN regions that realize peace. Thus, the author argues the importance of the role of ASEAN countries as a mediator point towards peace and diplomacy in resolving conflicts over human rights violations through cooperation and reducing humanitarian tensions so as to create equality, togetherness between people.